Cytotoxicity and genotoxicity of pulp capping materials in two cell lines - Camargo, S. E. A. [UNESP]; Camargo, C. H. R. [UNESP]; Hiller, K.-A.; Rode, S. M. [UNESP]; Schweikl, H.; Schmalz, G. (Wiley-Blackwell Publishing, Inc, 2009)
The aim of this study was to evaluate the cytotoxicity and genotoxicity of the new castor oil bean cement (COB) material in comparison to commonly used pulp capping materials.Specimens of COB, calcium hydroxide (Hydro C), and mineral trioxide aggregate (white and gray MTA) were extracted in culture medium (91.6 mm(2) sample surface mL(-1)). Transfected human pulp cells (tHPCs) were exposed to dilutions of the extracts for 1 h, and the generation of reactive oxygen species (ROS) was determined by flow cytometry (FACS) using H(2)DCF-DA as a dye. Survival of tHPCs was measured photometrically using a crystal violet assay after a 24-h exposure period. Genotoxicity as indicated by the formation of micronuclei in V79 cells, and the modification of the normal cell cycle by extracts of the materials was analysed by FACS.Clear cytotoxic effects were detected only with extracts of Hydro C under the current experimental conditions. The two MTA preparations induced an insignificant reduction in the number of cells. In contrast, the extracts of COB slightly induced cell proliferation. Extracts of Hydro C caused a twofold increase in ROS production, whilst the other tested materials were ineffective. An increase in the number of micronuclei was not detected with any material tested; Hydro C slightly increased the number of cells in G1 and G2.The COB and the two MTA preparations did not negatively influence cell survival or ROS production and may thus be further considered for pulp capping studies.
Keywords: cytotoxicity; genotoxicity; pulp capping materials; reactive oxygen species